Enhancement of Anaerobic Digestion to Treat Saline Sludge from Recirculating Aquaculture Systems - Guo-zhi Luo; Niannian Ma; Ping Li; Hong-xin Tan; Wenchang Liu (The Scientific World Journal)
The effectiveness of carbohydrate addition and the use of ultrasonication as a pretreatment for the mesophilic anaerobic digestion of saline aquacultural sludge was assessed. Analyses were conducted using an anaerobic sequencing batch reactor (ASBR), which included stopped gas production attributed to the saline inhibition. After increasing the C : N ratio, gas production was observed, and the total chemical oxygen demand (TCOD) removal efficiency increased from 75% to 80%. The TCOD removal efficiency of the sonication period was approximately 85%, compared to 75% for the untreated waste. Ultrasonication of aquaculture sludge was also found to enhance the gas production rate and the TCOD removal efficiency. The average volatile fatty acid (VFA) to alkalinity ratios ranged from 0.1 to 0.05, confirming the stability of the digesters. Furthermore, soluble chemical oxygen demand (SCOD), VFA, and PO43- concentrations increased in the effluents. There was a 114% greater gas generation during the ultrasonication period, with an average production of 0.08 g COD/L·day−1.